Analogical Understanding of the Ragone plot and a New Categorization of Energy Devices. (June 2016) - Lee, Sang C.; Jung, Woo Young
Abstract: The main function of energy devices is to generate power and store energy. The typical storage devices are battery and capacitor; generation devices are internal combustion engine (ICE), gas turbine, and fuel cell. Every kinds of energy devices can be compared together in the Ragone plot with respect to specific energy and specific power. Moreover, some difficulties to make position of solar cell in the Ragone plot are proposed. In this paper some analogical explanation is given to understand the underlined meaning. The barrel model is introduced to make analogy; the specific volume and area to the specific energy and specific power. The relationship between the curves depicted in axises of cell voltage with current and specific energy with specific power is tried to be shown in the viewpoint of device operation conditions. Also, the limitation of the Ragone plot is discussed to encompass the existing energy devices to be utilized as the standard benchmarking chart.